Conversational Strategies Used by Kim Kardashian and Kris Jenner at The New York Times DealBook Conference - Michelle Jevida; Esther Harijanti Kuntjara (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This study analyzed the conversational strategies of Kim Kardashian and Kris Jenner at The New York Times conference, focusing on their business-related discussions and exploring similarities and differences based on age and status. Following Coates' (2013) theory, seven strategy aspects were examined: minimal responses, hedges, tag questions, questions, commands and directives, swearing and taboo languages, and compliments. Using a descriptive qualitative approach, the study identified the strategies employed by each speaker. Kim Kardashian used five strategies, while Kris Jenner used six. Overall, the findings indicated more similarity than difference in their conversational strategies, suggesting there are influences from context, status, and age.